Comparative Study of a GEM-based Fast Neutron Detector Using 4He/CO2 and 4He/CO2/C4H10 Gas Mixtures - Kiadtisak Saenboonruang (Science Faculty of Chiang Mai University, 2019)
1H- or 4He-contained gas mixtures are usually used to detect fast neutrons, which relies on elastic scattering between fast neutrons and light gas molecules. In this research, gas mixtures of 4He/CO2 (80:20 and 70:30) and 4He/CO2/C4H10 (70:23:7) were flowed through a 10 cm×10 cm triple-Gas Electron Multiplier (GEM) detector at a constant flow rate of 3.0 L/hr in order to detect fast neutrons. Comparisons of relative efficiencies, relative gains, and detection uniformity for all gas types were investigated by measuring signal counts and signal amplitudes. Results showed that a gas mixture of 4He/CO2 (80:20) had the highest relative efficiency and relative gains amongst all gas mixture types. In terms of detection uniformity, detection efficiency at the center of the active area was approximately 20% higher than areas close to the detector edges. Details of basic knowledge of GEM, experimental procedures, results and discussion are included in this article.